CONSTRUCTING AND NEGOTIATING IDENTITY IN TALK-IN-INTERACTION: A SOCIOPRAGMATIC FRAMEWORK FOR ANALYZING PRAGMATIC STRATEGIES - Agus, Cecep; Iswandi, Fedro (Journal of Pragmatics and Discourse Research, 2025)
This study uses a Conversation Analysis (CA) framework with a sociopragmatic orientation to investigate how individuals construct, negotiate, and reframe social identities through pragmatic strategies in everyday conversation. Unlike previous studies, which treat identity as a background variable, this research treats it as an emergent, interactional accomplishment. Drawing on naturally occurring conversations from various contexts: peer, familial, romantic, collegial, and institutional, the current study identifies consistent patterns in using pragmatic resources, such as stance-taking, humour, mitigation, epistemic markers, and politeness strategies. The study's unique theoretical contribution lies in articulating three interrelated models: (1) Relational-Pragmatic Identity Construction (RPIC) Theory, which explains how pragmatic strategies constitute identity in context-sensitive relational terms; (2) Contextual Identity Indexicality (CII) Hypothesis, which theorises that pragmatic features act as indexicals that signal fluid, situational identities; and (3) Epistemic Identity Alignment Model (EIAM), which conceptualises identity negotiation as involving shifts in epistemic stance within asymmetrical interactions. Together, these frameworks advance the understanding of identity as a performative and context-dependent process embedded in the micro-sequential structures of conversation. The findings extend existing theories by demonstrating that pragmatic resources function not merely to manage face, but also as primary mechanisms of identity construction across relational contexts